2018
DOI: 10.1016/j.ultsonch.2017.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of ultrasonic-assisted crude oil demulsification based on acoustic field distribution data

Abstract: Water removal is an essential step during crude oil production due to several problems such as increased transportation costs and high corrosion rate due to dissolved salts. Indirect low frequency ultrasonic energy (US), using baths, has been recently proposed as an effective alternative for crude oil demulsification. However, the reactor position during sonication and its influence on the demulsification efficiency for crude oil has not been evaluated. In this sense, the aim of this study was to develop an au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Experiments for USAE were performed with an ultrasound bath, an ultrasound probe or a cup horn system coupled to an ultrasonic processor. Each system was set to allow better incidence of ultrasound, following previous work . The operational parameters of the ultrasound systems are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Experiments for USAE were performed with an ultrasound bath, an ultrasound probe or a cup horn system coupled to an ultrasonic processor. Each system was set to allow better incidence of ultrasound, following previous work . The operational parameters of the ultrasound systems are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…At a frequency of >45 kHz, there was no evidence of crude oil demulsification. In the work of Pedrotti et al [150], a demulsification efficiency of up to 93% was attained at 15 min of sonication (100% amplitude). Pedrotti et al [150] proposed the use of indirect low-frequency ultrasonic energy for the demulsification of crude oil.…”
Section: Ultrasonic Demulsificationmentioning
confidence: 97%
“…In the work of Pedrotti et al [150], a demulsification efficiency of up to 93% was attained at 15 min of sonication (100% amplitude). Pedrotti et al [150] proposed the use of indirect low-frequency ultrasonic energy for the demulsification of crude oil. The results showed that a higher demulsification efficiency (up to 93%) was attained in the most intense acoustic regions compared with that positioned in the less intense acoustic field regions.…”
Section: Ultrasonic Demulsificationmentioning
confidence: 97%
“…Therefore, it is generally believed that the ultrasonic treatment time is controlled within 30 minutes; the longer the sedimentation time, the more dehydration effect, but as time goes on, the trend of increasing dehydration rate is gradually decreasing. [77][78][79][80] Antes et al 81 carried out a demulsification test on heavy oil emulsions with water content of 12%, 35%, and 50% at frequencies of 25,35,45,130,582,862, and 1146 kHz, respectively. When the frequency is lower than 45 kHz, indirect application of ultrasonic waves can cause instability of the W/O emulsion, and demulsification is observed in a short time (15 minutes) and a relatively low temperature (45°C), which is attributed to ultrasonic cavitation caused by ultrasonic cavitation, leading to an increase in mechanical effects and destroying the stress balance at the interface film.…”
Section: Tomacmentioning
confidence: 99%
“…However, as the ultrasonic treatment time increases, the dehydration rate is almost unchanged. Therefore, it is generally believed that the ultrasonic treatment time is controlled within 30 minutes; the longer the sedimentation time, the more dehydration effect, but as time goes on, the trend of increasing dehydration rate is gradually decreasing 77–80 . Antes et al 81 carried out a demulsification test on heavy oil emulsions with water content of 12%, 35%, and 50% at frequencies of 25, 35, 45, 130, 582, 862, and 1146 kHz, respectively.…”
Section: Research Status and Development Trend Of Demulsification Metmentioning
confidence: 99%